OPINI AUDIT ATAS PENGUNGKAPAN LAPORAN KEUANGAN PEMERINTAH KABUPATEN DI SULAWESI SELATAN - Ayu Puspita Sari; Muhammad Adil (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2020)
This research aims to analyze whether the audit opinion relates to the disclosure of the financial statements of the District government in South Sulawesi; This research uses secondary data that is qualitative descriptive in the content analysis method (contents) to calculate the score of the disclosure of the District government's financial reporting. The results of the study showed that the audit opinion relates to the disclosure of the District government's financial statements in South Sulawesi.